Ranolazine as you have never seen it before: an antiarrhythmic for atrial fibrillation. (25th November 2020) - Sousa, J.P; Puga, L; Ribeiro, J; Lopes, J; Saleiro, C; Gomes, R; Campos, D; Lourenco, C; Goncalves, L
Abstract: Background: Currently available pharmacological options for rhythm control in atrial fibrillation (AF) are overshadowed by suboptimal efficacy and both frequent and potentially severe adverse events. Recent studies have added evidence to the hypothesis that ranolazine might exert antiarrhythmic effects, particularly in atrial tachyarrhythmias. Purpose: To perform a systematic review with meta-analysis in order to ascertain the potential role of ranolazine in the management of AF. Methods: We systematically searched MEDLINE, Embase and Scopus for randomized controlled trials (RCTs) and cohort studies addressing the association between ranolazine and AF outcomes, published up until December 1, 2019. The primary endpoint was incidence of AF, which was evaluated under a ranolazine versus placebo design. In this regard, patients in the setting of postcardiac surgery were further investigated separately. Secondary endpoints included AF cardioversion outcomes, which were addressed through comparison between ranolazine plus amiodarone and amiodarone alone for proportional efficacy and temporal requirements (time-to-cardioversion). The latter analysis was also undertaken in a dose-sensitive fashion (≤1000mg vs. 1500mg of ranolazine). Tertiary endpoints covered AF burden and episodes, in paroxysmal AF patients, and safety outcomes, namely death, QTc interval prolongation and hypotension. Study-specific odds ratios (ORs) were pooled using meta-analytic techniques with a random-effects model. Results: A total of 10 RCTs comprising 8.109 participants and 3 cohort studies encompassing 37.112 patients were regarded as eligible for evaluation. Ranolazine was found to attenuate patients' odds of developing AF (OR 0.53, 95% CI: 0.41–0.69, p<0.001, i2=58%). This effect held true, with an even larger effect size, in the context of post-cardiac surgery (OR 0.34, 95% CI: 0.16–0.72, p=0.005, i2=64%). Ranolazine increased the chances of successful AF cardioversion when added to amiodarone over amiodarone alone (OR 6.67, 95% CI: 1.49–29.89, p=0.01, i2=76%), while significantly reducing time-to-cardioversion [SMD 9.54h, 95% CI: −13.3–5.75, p<0.001, i2=99%]. Interestingly, cardioversion was faster with ≤1000mg of ranolazine (SMD −13.16h, 95% CI: −15.07–11.25, p<0.001, i2=95%) than with 1500mg (SMD −3.57h, 95% CI: −5.06–2.08, p<0.001, i2=23%). In paroxysmal AF, ranolazine was also proved to significantly reduce both AF burden and episodes. There were no safety signals regarding mortality odds, QTc interval prolongation (mostly clinically insignificant) and hypotension (mostly transitory). Conclusion: Current evidence suggests that ranolazine provides an effective and safe option for a chemical rhythm control strategy in AF management, a field in which medical breakthroughs are desperately needed. Funding Acknowledgement: Type of funding source: None